Toxicity of Sclerocarya birrea and Azadirachta indica extracts against maize weevil Sitophilus zeamais Motchulsky (Coleoptera: Curculionidae) in storage - Babarinde, SA; Petinrin, MO; Adeleye, AD; Ajani, BS (Bangladesh Journal of Scientific and Industrial Research, 2017)
Toxicity of Sclerocarya birrea A. Rich. (Anacardiaceae) leaf and bark and Azadirachta indica A. Juss (Meliaceae) leaf extracts against Sitophilus zeamais Motchulsky (Coleoptera: Curculionidae) was evaluated under the laboratory conditions (77±4% relative humidity and 27±3°C temperature). When extracted doses were compared, mortality was dose- and exposure period-dependent. At 1 DAT, A. indica leaf extract had significantly (p<0.05) higher mortality (12.50-15.00%) than that of S. birrea bark extract (5.00-15.50%). However at 5 DAT, when 0.45 ml/33 cm2 was applied, mortality was not significantly (p>0.05) different and ranged from 91.25 to 97.5% for all the botanicals. When the extracting solvents were compared, mortality was exposure period-dependent with highest percentage mortality (99.17%) recorded at 5 DAT in S. birrea petroleum ether leaf extract, which was significantly higher than that of mortality observed in filter paper treated with the petroleum ether extracts of other botanicals. However, there was no significant difference in the effect of the two studied solvents. The results highlight the insecticidal potentials of the selected Nigerian-grown botanicals against maize weevil and recommend them as component of weevil Integrated Pest Management, in the areas where the botanicals are abundant. Bangladesh J. Sci. Ind. Res. 52(4), 337-342, 2017